Transcriptomic and metabolomic analysis of the antibacterial mechanism of sanguinarine against Enterobacter cloacae in vitro - Ting Yang; Haojie Sha; Wenlu Bi; Jianguo Zeng; Dingding Su (BMC Microbiology)
Abstract Background Enterobacter cloacae (E. cloacae) is a notorious pathogen that poses serious threat to both human and animal health, causing severe gut infections and contributing to food spoilage. Traditional chemical treatment have led to increased drug resistance and environmental pollution. This study investigates the potential of Sanguinarine (SAN), a natural plant extract, as an alternative to chemical antibiotics. Results In light of the escalating issue of antibiotic resistance, we examined the antibacterial efficacy and mechanisms of SAN against E. cloacae in vitro. Our findings revealed a minimum inhibitory concentration (MIC) of 100 µg/mL for SAN. Scanning electron microscopy (SEM) demonstrated substantial morphological disruptions in E. cloacae cells treated with SAN. Concurrently, a significant increase in absorbance at 260 nm suggested nucleic acid leakage, indicative of compromised cell membrane integrity. Comprehensive transcriptomic and metabolomic analyses revealed that SAN primarily disrupts amino acid synthesis and energy metabolism pathway in E. cloacae. Conclusions SAN exhibited potential antibacterial activity against E. cloacae, which can effectively inhibit its growth and disrupt its bacterial morphology and exert antibacterial effect through multiple pathways, and can be used as a potential substitute for antibiotics.